Nutrition Therapy in Post-Hartmann’s Procedure Patients in The Intensive Care Unit - Palupi, Isnafianing; Adiyanto, Bowo; Wisudarti, Calcarina Fitriani Retno (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2025)
Background: The Hartmann procedure is a surgical procedure for treating colorectal cancer that is widely used in emergencies because it is fast and has a minimal risk of anastomotic leakage. This procedure is usually performed on rectosigmoid cancer. Colorectal cancer patients who undergo gastrointestinal surgery are considered at risk of malnutrition, so adequate nutritional therapy is needed.Case: We report a 51-year-old male patient who came to the intensive care unit (ICU) with an unconscious condition, was intubated, received Norepinephrine support, and had a reddish black product in the nasogastric tube (NGT). The patient was referred with a diagnosis of post-operative Hartmann’s procedure day-3 (D-3) for indications of high obstructive ileus due to rectosigmoid tumor, septic shock, acute kidney injury (AKI), and peptic ulcer. During treatment in the ICU, the patient received antibiotic therapy (Meropenem and Metronidazole), proton pump inhibitors (PPIs), and parenteral nutrition via a central venous catheter (CVC).Discussion: Parenteral nutrition was given from the beginning of admission to the ICU because oral and enteral nutrition could not be provided due to gastrointestinal bleeding (peptic ulcer). Moreover, the patient was considered at risk of malnutrition with evidence of critical illness more than 48 hours post-gastrointestinal surgery due to cancer. Also, there was a post-operative fasting period, usually for several hours to 1-2 days, depending on the patient's condition.Conclusion: Nutritional therapy, as part of the management of critically ill patients, should be given at the right time, in the most effective way, and in appropriate doses for each individual to avoid malnutrition during treatment.